Characterisation of indentation microstructures for porous SOFC cathodes. Issue 1 (January 2020) - Chen, Zhangwei; Gong, Zhiyuan; Li, Ziyong; Zhu, Zhongqi; Qu, Piao; Lao, Changshi; Wang, Pei; Liu, Changyong; Atkinson, Alan
Abstract: In this study, high-resolution focused ion beam sectioning assisted with SEM imaging was used to study the indentation microstructures of porous bulks and films of a solid oxide fuel cell cathode material (La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ ) sintered at different temperatures. The crack morphologies and pore-filling densification caused by crushing of particle networks were studied in details. Analysis showed distinct permanent deformation mechanisms of the indentation microstructures between porous bulks and films. Whilst remarkable porosity gradient was found for the porous films under both Berkovich and spherical indenters, the porous bulks were found to behave more like dense materials. Results also showed that radial cracks induced by Berkovich indentation on the bulks could not generate observable pop-in/pop-out events in the loading-unloading curves. However, when indenting with the spherical indenter on a thick film, the shear sliding of the particle networks immediately under the indenter could cause phenomenal disruption in the loading unloading curves shown.